Risk Analysis in the Palm Oil Harvesting Process Using the Mix Method (Case Study at PT XYZ South Kalimantan) - Rahyang Niskala Wastu Kencana; Iriani Iriani (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2025)
The harvesting process in oil palm plantations is one of the critical stages that greatly affects the productivity and quality of production results. The risks that arise in this process, both from operational risks, environmental risks, and human resource risks can have a significant impact on operational efficiency. This study aims to determine the level of risk in the harvesting process of oil palm products at PT XYZ South Kalimantan and to find out the proposed improvements that are in accordance with the problems faced using the mixed method, which combines qualitative and quantitative techniques. The results of the study showed that there were three levels of risk with the highest risk values. Namely the risk of work accidents with a risk value of 20 and a high risk level, the risk of damage to harvesting equipment with a risk value of 10 and a moderate risk level, and the risk of replacing harvesting equipment with a risk value of 10 and a moderate risk level. These three risks are risks with the highest priority level of handling. For this reason, it is recommended to focus on human control and SOPs, control of tools and procedures, and change management. With proper risk management, the harvesting process can run more efficiently, safely, and sustainably.